ANALISIS SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN GURU TERBAIK DENGAN MENGGUNAKAN METODE WASPAS DI SMK NEGERI 3 MUARO JAMBI - Huda Aminuddin, Fattachul; Nasritasari, Nofi (LP2M Universitas Nurdin Hamzah, 2023)
SMK Negeri 3 Muaro Jambi is a vocational high school in Taman Rajo District, Muaro Jambi District, Jambi Province. At the end of each school year, The principal of SMK Negeri 3 Muaro Jambi has been selecting teachers achievement. The principal identifies outstanding teachers at SMK Negeri 3 Muaro Jambi so far is still subjective. This selection was deemed less effective because it was also influenced by factors outside of the provisions of the criteria, resulting in conflict and decision results does not correspond to the actual decision results. Criteria used such as length of service, last education, class rank, competency and discipline of teachers. The research aims to examine related methods on Decision Support Systems (DSS) using Weighted Aggregated Sum Product Assessment (WASPAS). The basic concept of the method namely carrying out a complex calculation process according to certain criteria has been determined to obtain ranking results. The results obtained are that The application of the WASPAS method can provide school principals with the ability to determine one of the outstanding teachers based on the highest ranking results.